Determinants of Human Capital and Public Sector Finance on Development Inequality in East Kalimantan Province - Rahmawati, Thariska Devi; Arif, Muhammad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Inequality occurs due to differences in characteristics in each region, in terms of natural resources, human resources, and capital resources. The level of development inequality in Indonesia in recent years has increased. This research aims to determine the influence of the human development index, foreign investment, domestic investment, capital expenditure, general allocation funds, and special allocations on development inequality in East Kalimantan province in 2018-2022. This research is quantitative research using secondary data for each province from 2018-2022. The data analysis used is data regression analysis using the Random Effects Model (REM) approach. The results of this research show that the Human Development Index, foreign investment, and domestic investment have a positive and significant effect, while capital expenditure, Special Allocation Funds, and General Allocation Funds do not affect development inequality in East Kalimantan Province in 2018-2022.